Virtual reality haptic device for dental illness treatment - Deusdado, Leonel (2023)
Schizophrenia is a mental disorder that alters mental functioning and can cause hallucinations, mental disorientation, and a variety of other symptoms, which results in a separation of schizophrenics from society. Despite the fact that the condition has been known about for a long time, there is still an urgent need for research and testing to develop better therapies. Virtual reality (VR) has had interesting outcomes when used to treat illnesses, and it is gradually emerging as a viable technical choice for the healthcare sector due to its immersion, which offers better and more intense user experiences. Once linked to a serious game, it can introduce the user to a number of situations that, when combined with medical assistance, aid in their rehabilitation and treatment. The use of haptic devices enhances VR immersion by enabling users to comprehend virtual environments with greater nuance, which increases their level of believing in the new environment they are in. When used in conjunction with VR, it can improve the efficacy of the treatment, making its use viable for the treatment of psychic diseases. The goal of this research is to develop haptic vest interactions using a three-dimensional virtual testing scenario to support and improve the use of VR for rehabilitation and therapy for schizophrenia. The established functionalities can be applied to a further serious game with the same focus.